Hydrogen-bond-driven supramolecular self-assembly of diacetylene derivatives for topochemical polymerization in solution. Issue 11 (6th February 2020) - Fan, Jianqiang; Xu, Xiao; Yu, Wei; Wei, Zhihong; Zhang, Dengqing
Abstract : We report here photoinduced topochemical polymerizations of diacetylene-derivatized compound by the introduction of amide functions as the structure directing agent in solution. Abstract : We report here on a set of diacetylene-derivatized compounds by the introduction of amide functions as structure directing agents. Facilitated by hydrogen-bonding, the ordered supramolecular nanofibers comprising 2 placed the reactive diynes at appropriate positions to allow for topochemical polymerizations upon photoirradiation in methylcyclohexane. However, no polymerization reaction occurred in 1 because phenyl groups were too close to the diacetylene moiety, which may limit the geometry of diacetylene functions required for 1, 4-polymerization and inhibit the topochemical polymerization. This mild, additive-free and solution-processable polymerization of diacetylene monomers is particularly promising because it enables a wider range of applications in patterning and processing of π-conjugated materials and the rigidification of conjugated polymeric networks.